2009
DOI: 10.1186/1475-2875-8-26
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial activities of Andrographis paniculata and Hedyotis corymbosa extracts and their combination with curcumin

Abstract: Background: Herbal extracts of Andrographis paniculata (AP) and Hedyotis corymbosa (HC) are known as hepato-protective and fever-reducing drugs since ancient time and they have been used regularly by the people in the south Asian sub-continent. Methanolic extracts of these two plants were tested in vitro on choloroquine sensitive and resistant (MRC-pf-303) strains of Plasmodium falciparum for their anti-malarial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 28 publications
2
77
2
2
Order By: Relevance
“…(Rubiaceae), etc. (Sharma & Sharma, 2000;Dua et al, 2004;Mishra et al, 2009). The assay is primarily based on the inhibition of the mature ring stages of the parasites, i.e., schizonts.…”
Section: Discussionmentioning
confidence: 99%
“…(Rubiaceae), etc. (Sharma & Sharma, 2000;Dua et al, 2004;Mishra et al, 2009). The assay is primarily based on the inhibition of the mature ring stages of the parasites, i.e., schizonts.…”
Section: Discussionmentioning
confidence: 99%
“…Mishra et al (2009) have reported on the methanolic extract of Andrographis paniculata which was tested in vitro on choloroquine-sensitive and resistant strains of Plasmodium falciparum for its antimalarial activity. In vivo activity demonstrated higher antimalarial effect at low concentration within 24-h incubation period (Nik et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…For example is the discovery of new antimalarial artemisinin and its derivatives from Artemisia annua that has been used in China for centuries traditionally. This proves that the medicinal plants is a natural source of new antimalarials that still need to be explored (Li and Wu, 1998 (Mishra et al, 2009), Enicostemma littorale (Soni and Gupta, 2009) and Quassia amara L. (Houel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%